Shoe Dog : A memoir by the creator of NIKE - ปังศรีอุทัย มุนิน (บรรณศาสตร์ มศว, 2018)
Shoe Dog’ is the memoir of Phil Knight is the founder and CEO of NIKE. He shares the inside story of the company’s early days as an intrepid start-up and its evolution into one of the world’s most iconic, game-changing, and profitable brands. Phil Knight started his shoe company, in 1963 by selling shoes from the trunk of his Plymouth Valiant. He grossed around 8,000 that first year and this was the beginning of a now 30 billion dollar company called Nike. The book is peppered with historical, spiritual and inspirational quotes that provide motivation for business and for life. If you read this book you will get the impression “What did he actually do?” for NIKE to become so successful. It’s a great source for how to start a business or what should to do for entrepreneurs. JUST DO IT. Those words are the life story of Phil Knight ‘Shoe Dog’ เป็นหนังสือที่เขียนโดย Phil Knight ผู้ก่อตั้งแบรนด์กี่ฬาระดับโลกอย่าง NIKE เขาได้เล่าเรื่องราวกว่าที่จะมาเป็น NIKE ตั้งแต่จุดเริ่มต้นของแบรนด์ ไม่ว่าจะเป็นการเปลี่ยนเกมส์ทางธุรกิจ และการทำกำไรอย่างมหาศาล โดยเริ่มจากการเปิดท้ายรถขายรองเท้า จนทุกวันนี้มีรายได้สูงสุดถึง 30,000 ล้านเหรียญดอลลาร์สหรัฐ หนังสือเล่มนี้จะเต็มไปด้วยเรื่องราวและข้อคิดดี ๆ ที่สร้างแรงบันดาลใจ ทั้งทางด้านธุรกิจและการดำเนินชีวิต หากคุณเป็นผู้ที่หลงรักในแบรนด์ NIKE หรือกำลังมองหาแรงบันดาลในในการดำเนินธุรกิจ ‘Shoe Dog’ เป็นหนึ่งในหนังสือที่ควรค่ากับการอ่านมากที่สุดเล่มหนึ่ง